2019
DOI: 10.1152/ajplung.00552.2017
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility group box-1 protein from CC10+ club cells promotes type 2 response in the later stage of respiratory syncytial virus infection

Abstract: The type 2 immune response, induced by infection of respiratory syncytial virus (RSV), has been linked to asthma development, but it remains unclear how the response is initiated. Here, we reported that the high-mobility group box-1 (HMGB1) protein promotes the type 2 response in the later stage of RSV infection. In mice, we found that type 2 cytokines were elevated in the later stages, which were strongly diminished after administration of anti-HMGB1 antibodies. Further investigation revealed that HMGB1 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Indeed, in nasopharyngeal aspirates from children with HRSV bronchiolitis HMGB1 levels are 10 times higher compared to children without lower respiratory tract infections and the HMGB1 level is correlated with clinical severity. Moreover these findings can pinpoint long-term consequences for infected children to develop asthma in their adulthood (Chen et al, 2019). Innate immune arm will induce the activation of the adaptive immunity in infectious diseases.…”
Section: In Vivo Experimental Modelsmentioning
confidence: 91%
“…Indeed, in nasopharyngeal aspirates from children with HRSV bronchiolitis HMGB1 levels are 10 times higher compared to children without lower respiratory tract infections and the HMGB1 level is correlated with clinical severity. Moreover these findings can pinpoint long-term consequences for infected children to develop asthma in their adulthood (Chen et al, 2019). Innate immune arm will induce the activation of the adaptive immunity in infectious diseases.…”
Section: In Vivo Experimental Modelsmentioning
confidence: 91%
“…The majority of data on this mediator release in response to a stimulus is derived from in vivo murine models or in vitro culture; for instance, IAV, RSV, and hRV are all potent inducers of IL-33 release in mice and from human bronchial epithelial cells (hBECs) in vitro (Josset et al, 2014;Kearley et al, 2015). Elevated TSLP, HMGB-1, and IL-33 are seen in the nasopharynx of infants with hRV-and RSV-associated bronchiolitis and IL-33 in nasal aspirates of children with severe IAV infection, all likely indicative of the particular viral strains being encountered for the first time (Chen et al, 2019;García-García et al, 2017;Guo et al, 2018;Perez et al, 2014;Saravia et al, 2015). Elevated concentrations of IL-25 and IL-33 are likewise seen in the airways of previously seronegative adults challenged experimentally with a hRV, particularly in subjects who are also asthmatic (Beale et al, 2014;Jackson et al, 2014;Ravanetti et al, 2019).…”
Section: First Immune Responders: Ecs and Am Responsesmentioning
confidence: 99%
“…The pulmonary inflammatory immune response plays an important role in the outcome of RSV infection. It has been clinically shown that the level of HMGB1 in nasopharyngeal aspirates of children with bronchiolitis caused by RSV was significantly higher than that of patients without lower respiratory tract infection and was correlated with clinical severity 34 . RSV strongly induces HMGB1 expression both in vivo and in vitro, and the inhibition of HMGB1 blocks the upregulation of HMGB1 in immortalized or primary human bronchial epithelial cells infected with RSV; this was associated with reduced viral replication 34,35 .…”
Section: Role Of Hmgb1 In Pediatric Diseasesmentioning
confidence: 99%
“…It has been clinically shown that the level of HMGB1 in nasopharyngeal aspirates of children with bronchiolitis caused by RSV was significantly higher than that of patients without lower respiratory tract infection and was correlated with clinical severity 34 . RSV strongly induces HMGB1 expression both in vivo and in vitro, and the inhibition of HMGB1 blocks the upregulation of HMGB1 in immortalized or primary human bronchial epithelial cells infected with RSV; this was associated with reduced viral replication 34,35 . In addition, it was also shown that RSV‐infected human airway epithelial cells release HMGB1 in a paracrine manner to activate immune cells to secrete inflammatory mediators to promote the inflammatory cascade that depends on TLR4/NF‐κB signaling pathway activation, 36,37 which may provide a new strategy for the prevention of the RSV‐induced inflammatory response at the molecular level.…”
Section: Role Of Hmgb1 In Pediatric Diseasesmentioning
confidence: 99%